Effect of normal and atheromatous aortic tissue on platelet aggregation in vitro. Issue 4 (July 1966) - Prentice, C. R. M.; McNicol, G. P.; Douglas, A. S.
Abstract : An investigation was made into the platelet-aggregating ability of human aortic tissue. It was found that potent aggregating substances are present in the vascular wall but that the degree and character of platelet aggregation produced was dependent on the method employed in the preparation of the tissue for study. The supernatants of aortic tissue homogenates were found to produce potent irreversible platelet aggregation that occurred after a latent period of one to two minutes. The activity was heat labile, destroyed by collagenase, sedimented by ultracentrifugation, and was considered to be identical or similar to collagen. An extract obtained by boiling aortic tissue with saline was found to cause less powerful reversible platelet aggregation that occurred within 15 to 30 seconds' contact with platelets; the activity was not affected by heating, incubation with collagenase, or ultracentrifugation, and was considered to be due to adenosine diphosphate. Atheromatous aortic tissue when extracted by either method was found to contain less than one half of the potency of normal tissue in causing platelet aggregation.